PENGARUH PENAMBAHAN PATI JAHE HASIL SAMPING PEMBUATAN JAHE INSTAN PADA MUTU KUE KERING (Jurnal Teknologi Pangan, 2013)
The  study aims to determine  effects  of  the  adddition  of    ginger  starch  byproduct  from  instant ginger  production  on  cookies  quality  produced. Research    carried  out  by using a  mixture of  85  % flour and 15 % starch ginger (treatment A), a mixture of flour 80 % and 20 % starch ginger (treatment B) and a mixture of 75 % flour and 25 %  starch ginger (treatment C) From the results showed that the mixture  of  flour and ginger starch byproduct of  making instant  ginger did  not significantly  affect the  color, flavor  and texture  of the  resulting cookies, while  the aroma of real  effect. Treatment  of a mixture  of flour  and ginger starch byproduct of  making instant  ginger cookies are preferred for the consumer is in treatment C, with chemical  and microbiological test  results on  average were: water content of 1.79% w / w, ash content 0.97 % w / w, protein 7.89% w / w, Total Number Plate 6.9 x102 colonies / g. While  the  results  of organoleptic  tests averaged: color 3.20 (usual), taste 3.70 (like), aroma 3.90 (like) and texture 3.80 (like).Keywords: ginger starch, cookies